Deiksis Waktu dan Tempat dalam Novel Tentang Kamu Karya Tere Liye serta Implikasinya terhadap Materi Pembelajaran Teks Cerita Pendek di SMP - Rubi Yanti; Petrus Poerwadi; Lazarus Linarto; Alifiah Nurachmana; Syarah Veniaty (Universitas Palangka Raya, 2024)
The purpose of this study is to describe (1) the form of time deixis found in the novel Tentang Kamu by Tere Liye, (2) the form of place deixis found in the novel Tentang Kamu by Tere Liye, (3) the function of time deixis contained in the novel Tentang Kamu by Tere Liye, (4) the function of place deixis contained in the novel Tentang Kamu by Tere Liye, and (5) its implications for learning short story texts in junior high schools. This research is descriptive research using a qualitative approach with content analysis techniques. The data source in this research is the novel Tentang Kamu by Tere Liye. The data in it is in the form of words and phrases that contain elements of time and place deixis. The results of this research indicate the use of time and place deixis in the novel Tentang Kamu by Tere Liye. The form of time deixis is a word or phrase that refers to the time when an event occurs in a speech or story. Place deixis refers to the place referred to by the speaker or the place contained in the story. The function of time deixis is to indicate the time information of a speech or story which shows the past, present, and the future. The function of place deixis is to indicate the place of a speech or story which indicates a place close to the speaker, quite far from the speaker, and far from the speaker. The research has implications for learning short story texts KD 3.6 examining the structure and linguistic aspects of short stories read or heard in junior high school class IX.